2014
DOI: 10.4238/2014.march.26.9
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq reveals the downregulated proteins related to photosynthesis in growth-inhibited rice seedlings induced by low-energy N+ beam implantation

Abstract: ABSTRACT. Transcriptomic research based on RNA sequencing (RNA-seq) technology is innovative and will provide new opportunities and biological perspectives for the use of ion-beam implantation in plants. Using RNA-seq, transcriptomes of whole rice seedlings generated from seeds implanted with a low-energy N + beam were analyzed 96 h after planting. We identified 544 transcripts that were differentially expressed genes (DEGs) in the non-growth-inhibited sample implanted by an N + beam, including 262 upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…For example, depending on three rice mutant with reduced Cd contamination induced by 320 MeV/μ carbon ions, Ishikawa, et al [33]identified OsNRAMP5 gene in rice responsible for reducing Cd uptake. Using RNA-Seq technology, Chen, et al [34] found the down-regulated and injured genes related to photosynthesis contributed to the growth-inhibited rice mutant induced by 40 Kev/μ N + beam implantation. Through comparative analysis between wild type and utr319 rice mutant induced by carbon ions irradiation, TAKANO, et al [35]found that Os07g026510 gene in rice contributed to ultraviolet-B (UVB: 280–320 nm) tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, depending on three rice mutant with reduced Cd contamination induced by 320 MeV/μ carbon ions, Ishikawa, et al [33]identified OsNRAMP5 gene in rice responsible for reducing Cd uptake. Using RNA-Seq technology, Chen, et al [34] found the down-regulated and injured genes related to photosynthesis contributed to the growth-inhibited rice mutant induced by 40 Kev/μ N + beam implantation. Through comparative analysis between wild type and utr319 rice mutant induced by carbon ions irradiation, TAKANO, et al [35]found that Os07g026510 gene in rice contributed to ultraviolet-B (UVB: 280–320 nm) tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Plant gene expression can be changed by various stresses, such as ionizing radiation, UV-B, salinity, osmotic stress, and cold [15][16][17]. The N + beam down-regulated the expression of genes involved in the photosynthetic pathway [18], and carbon-ion beams highly up-regulated the expression of genes involved in signal transduction mechanisms [19]. Therefore, comparative analysis of transcripts is very effective in the investigation of gene expression changes in response to various ionizing radiations.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomics is a discipline that studies gene expression and transcriptional regulation in cells as a whole, and transcriptome analysis is necessary for exploring genome function and differential expression and plays an important role in studying plant growth and development ( Chen et al., 2014 ; Pankievicz et al., 2016 ; Stelpflug et al., 2016 ; Hsu and Tung, 2017 ; Ji et al., 2022 ). Metabolomics refers to the inheritance and development of genomics, transcriptomics and proteomics and can directly reflect the biochemical pathways and potential molecular mechanisms in organisms by elucidating the metabolites downstream of the genome as a whole and subsequently revealing the relevant metabolic pathways and metabolic networks ( Li et al., 2022 ; Prakash et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%